A synopsis of Braunia (Hedwigiaceae, Bryopsida) in Mexico, with the lectotypification of Braunia andrieuxii - de Luna, Efraín (Instituto de Ecología, A.C., 2021)
Background and Aims: Four species of Braunia are known in Mexico: Braunia andrieuxii, B. secunda, B. squarrulosa and B. plicata. A taxonomic study of the species of Braunia in Mexico has not been undertaken before. Moreover, among several “Andrieux” specimens currently available, there is no certainty as to which particular collection is the type. Methods: The four species of Braunia known in Mexico and neighboring areas in the southern United States of America, Central America and the Caribbean Islands were studied together for the first time. Based on over 450 collections from several herbaria, a taxonomic treatment and a key to the species of Braunia in this geographical region are presented. Key results: The four species are described and illustrated. A specimen Andrieux 23 located at BM is selected as the lectotype for B. andrieuxii, with isolectotypes in the herbaria BM and NY. A key is provided for the identification of the species of Braunia in Mexico, and neighboring USA, Central America, and the Caribbean. Conclusions: Morphological features most likely to be informative for the distinction of the four species in Mexico are the leaf margins, leaf apices, upper leaf cells, and sporophytes. The leaf apex is hyaline and dentate only in B. plicata, while it is concolorous and entire or scabrous in the other three species of Braunia from Mexico. The upper leaf cells are quadrate to short-rectangular in B. andrieuxii and B. plicata; whereas the upper leaf cells are elongate in B. secunda and B. squarrulosa.